Contralateral dissociation between neural activity and cerebral blood volume during recurrent acute focal neocortical seizures. Issue 9 (22nd July 2014) - Harris, Sam; Boorman, Luke; Bruyns‐Haylett, Michael; Kennerley, Aneurin; Ma, Hongtao; Zhao, Mingrui; Overton, Paul G.; Schwartz, Theodore H.; Berwick, Jason
Summary Objective Whether epileptic events disrupt normal neurovascular coupling mechanisms locally or remotely is unclear. We sought to investigate neurovascular coupling in an acute model of focal neocortical epilepsy, both within the seizure onset zone and in contralateral homotopic cortex. Methods Neurovascular coupling in both ipsilateral and contralateral vibrissal cortices of the urethane‐anesthetized rat were examined during recurrent 4‐aminopyridine (4‐AP, 15 mm, 1 μl) induced focal seizures. Local field potential (LFP) and multiunit spiking activity (MUA) were recorded via two bilaterally implanted 16‐channel microelectrodes. Concurrent two‐dimensional optical imaging spectroscopy was used to produce spatiotemporal maps of cerebral blood volume (CBV). Results Recurrent acute seizures in right vibrissal cortex (RVC) produced robust ipsilateral increases in LFP and MUA activity, most prominently in layer 5, that were nonlinearly correlated to local increases in CBV. In contrast, contralateral left vibrissal cortex (LVC) exhibited relatively smaller nonlaminar specific increases in neural activity coupled with a decrease in CBV, suggestive of dissociation between neural and hemodynamic responses. Significance These findings provide insights into the impact of epileptic events on the neurovascular unit, and have important implications both for the interpretation of perfusion‐based imaging signals in the disorder and understanding the widespread effects of epilepsy. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.